The glacial and sea-level history of Darling Peninsula, eastern Ellesmere Island - Gualtieri, Lyn (Géographie physique et Quaternaire, 1998)
Abstract The glacial history of Darling Peninsula is recorded by meltwater channels and lateral moraines deposited by local ice that extended seaward of the present coast during the last glacial maximum. Above these moraines, shelly till and erratics of both Greenland and Ellesmere Island prove nance record more extensive ice of unknown age. At the time of this more extensive ice cover, Ellesmere Island ice displaced Greenland ice from many parts of this coastline, as shown by the widespread absence of Greenland erratics and shelly tills above Holocene marine limit. The chronology of deglaciation is based on 14 C dates obtained on marine shells collected from either ice-contact deltas or raised beaches close to marine limit (79-88 m asl). Deglaciation began at least 7.5 ka BP and the distribution of ice on the peninsula was similar to present conditions by 6.0 ka BP. The reconstruction of the sea level history of Darling Peninsula contributes to the reconstruction of regional isobases drawn on 7.5 ka BP shorelines which locally reach 80-90 m asl.